The Effect of Cupping Therapy Towards Aggressive Behavior and Sleep Quality among Autism Spectrum Disorder (ASD) Patients - Hendra Sutysna; Miftahul Jannah; Adinda Raihana Sitorus (Indonesian Journal of Global Health Research, 2024)
Autism Spectrum Disorder characterized by behavioral issues like aggression, starts before age 3 and is linked to lead buildup. Poor sleep quality in ASD is due to circadian disruptions. Ongoing therapy is needed, and cupping therapy, releasing toxins like lead and affecting sleep quality via Nitric Oxide, is a complementary option. Objective: This study aimed to determine the effect of cupping therapy on sleep quality in people with Autism Spectrum Disorder (ASD). Methods: Observational correlative analysis with a prospective cohort study approach, the research sample was patients suffering from ASD in the city of Medan in 2023. Results: Based on the results of the Wilcoxon statistical test, the Sig. (2-tailed) 0.000 (p-value <0.05) which means there is a significant difference in aggressive behavior and sleep quality before and after being given cupping therapy in ASD sufferers. Conclusion: There is an effect of cupping therapy on aggressive behavior and sleep quality of Autism Spectrum Disorder (ASD) sufferers in the city of Medan in 2023.